Medical Best Practices and the Politics of Science Denial During the COVID-19 Pandemic (Global Journal of Medical Research, 2022)
An analysis of data from over 3,000 U.S. counties revealed that during the second year of the COVID-19 pandemic (March 1, 2021 -March 1, 2022) when vaccines were available to adults, the number of deaths per 100,000 residents was 3 times greater in counties where Trump received more than 75 percent of the vote compared to counties where he received 25 percent or less of the vote. It is clear that widespread misinformation and science denial, often politically motivated, had disastrous consequences. Rebuilding trust in science and medical expertise is vital if we hope to benefit from the important medical break throughs that are occurring.